2005
DOI: 10.3748/wjg.v11.i27.4173
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine stimulates cystic fibrosis transmembrane conductance regulator-mediated anion secretion in distal colon of rodents

Abstract: TMP may stimulate cAMP-dependent and CFTR-mediated Cl(-) and HCO(3)(-) secretion. This may have implications in the future development of alternative treatment for constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In myometrial cultures, both L. wallichii and TMP were unable to increase adenylate cyclase activity above basal levels, suggesting that neither can directly stimulate cAMP production in this tissue preparation. This is rather unexpected since we have previously shown that TMP can stimulate colonic anion secretion via cAMP pathway (He et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…In myometrial cultures, both L. wallichii and TMP were unable to increase adenylate cyclase activity above basal levels, suggesting that neither can directly stimulate cAMP production in this tissue preparation. This is rather unexpected since we have previously shown that TMP can stimulate colonic anion secretion via cAMP pathway (He et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Measurements were performed in the presence of a transepithelial Cl − gradient, in which the basolateral side solution contained (in mmol/L): 130 NaCl, 2.7 KCl, 1.5 KH 2 PO 4 , 1 CaCl 2 , 0.5 MgCl 2 , 10 Na–HEPES, pH 7.3, and 10 glucose; The apical side solution contained the same components except that 65 mmol/L NaCl was replaced by sodium gluconate and the concentration of CaCl 2 was increased to 2 mmol/L. The basolateral membrane was permeabilized with 250 μg/ml amphotericin B (He et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…The values are means ± SE, *P < 0.05, **P < 0.01. bacteria. In a previous study, it has been proved that TMP, which has been widely used clinically, could promote the secretion of HCO 3 - [8]. It is well known that the epithelial HCO 3 -secretion needs two steps: transportation through basolateral membrane and exit through apical membrane.…”
Section: Dicussionmentioning
confidence: 99%
“…The basolateral presence of bumetanide (0.1 mmol/l), the inhibitor of Na Recently it has been reported that TMP could increase the anion secretion of colonic mucosa [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation